ANALYSIS OF THE BOOK JĀMI’ AL-AḤĀDĪTS AL-QUDSĪYAH BY ‘ISHĀM AL-DĪN AL-SHABĀBITĪ - Hanief Monady; Baharudin Zamawi (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2021)
There are many works of classical, middle, and contemporary scholars who discuss the hadith of the prophet Muhammad SAW. These works are categorized into several types, namely primary hadith books, secondary hadith books, tertiary hadith books, mixed books with other Islamic religious sciences, and so on. One of these books, is a book entitled